Induced pluripotent stem cell model revealed impaired neurovascular interaction in genetic small vessel disease Cerebral Autosomal Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy - Zhang, Wenjun; Zhao, Xiangjun; Qi, Xuewei; Kimber, Susan J.; Hooper, Nigel M.; Wang, Tao (Frontiers in Cellular Neuroscience, 2023)
Cerebral Autosomal Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy (CADASIL) is the most common genetic small vessel disease caused by variants in the NOTCH3 gene. Patients with CADASIL experience recurrent strokes, developing into cognitive defect and vascular dementia. CADASIL is a late-onset vascular condition, but migraine and brain MRI lesions appear in CADASIL patients as early as their teens and twenties, suggesting an abnormal neurovascular interaction at the neurovascular unit (NVU) where microvessels meet the brain parenchyma. To understand the molecular mechanisms of CADASIL, we established induced pluripotent stem cell (iPSC) models from CADASIL patients and differentiated the iPSCs into the major NVU cell types including brain microvascular endothelial-like cells (BMECs), vascular mural cells (MCs), astrocytes and cortical projection neurons. We then built an in vitro NVU model by co-culturing different neurovascular cell types in Transwells and evaluated the blood brain barrier (BBB) function by measuring transendothelial electrical resistance (TEER). Results showed that, while the wild-type MCs, astrocytes and neurons could all independently and significantly enhance TEER of the iPSC-BMECs, such capability of MCs from iPSCs of CADASIL patients was significantly impaired. Additionally, the barrier function of the BMECs from CADASIL iPSCs was significantly decreased, accompanied with disorganised tight junctions in iPSC-BMECs, which could not be rescued by the wild-type MCs or sufficiently rescued by the wild-type astrocytes and neurons. Our findings provide new insight into early disease pathologies on the neurovascular interaction and BBB function at the molecular and cellular levels for CADASIL, which helps inform future therapeutic development.